Force Transmission by Minimal Focal Adhesion Complexes Induces Synthetic Cell Deformation - Huhn, Natalie; Hsu, Chiao Peng; Nast-Kolb, Timon; Hordeichyk, Arsenii; Bausch, Andreas R. (ACS Synthetic Biology, 2026)
Cells sense and respond to mechanical cues through focal adhesions–dynamic, multiprotein assemblies linking the actin cytoskeleton to the extracellular matrix. These complexes are essential to processes from cell migration to tissue morphogenesis, yet the minimal physical requirements for their force-transmitting and mechanosensing functions remain unclear. Here, we reconstitute minimal focal adhesion-like complexes in giant unilamellar vesicles (GUVs) using kindlin-2, talin-1, FAK, paxillin, zyxin, and VASP anchored to membranes containing PIP2 and integrin β1 tails. These assemblies nucleate and anchor actin filaments into networks spanning the vesicle surface. Upon addition of nonmuscle myosin IIa, actomyosin contraction thickens filament bundles, aligns the complexes, and deforms the GUVs, while the assemblies remain stably membrane-bound. Our findings show that actin recruitment, force transmission, and structural stability under load can emerge from defined protein-membrane interactions alone. This minimal, three-dimensional platform offers a controllable synthetic biology system for probing mechanosensing and engineering force-responsive biomimetic systems.
CRIS-Team Scopus Importer:2026-01-26
Keywords: actin; actomyosin; contractile force transmission; focal adhesion; protein complex; reconstitution